2022
DOI: 10.1038/s41388-022-02398-4
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 regulates glycolysis and energy production in multiple myeloma

Abstract: The transcription factor, forkhead box M1 (FOXM1), has been implicated in the natural history and outcome of newly diagnosed high-risk myeloma (HRMM) and relapsed/refractory myeloma (RRMM), but the mechanism with which FOXM1 promotes the growth of neoplastic plasma cells is poorly understood. Here we show that FOXM1 is a positive regulator of myeloma metabolism that greatly impacts the bioenergetic pathways of glycolysis and oxidative phosphorylation (OxPhos). Using FOXM1-deficient myeloma cells as principal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
(79 reference statements)
1
15
0
Order By: Relevance
“…We obtained similar results using NB-55 and NB-115, compounds that bind FOXM1 with high specificity and nanomolar affinity, enhancing its susceptibility to proteolysis and triggering proteasomal degradation (52). Similar to observations from myeloma, breast and ovarian cancer models (49,(53)(54)(55), both drugs caused dose-dependent suppression of proliferation and Foxm1 expression, while altering gene expression in a manner consistent with Foxm1 inhibition (Figure 6, D-F and Supplemental Figure 7, D and E). As with Foxm1 silencing, the response of c-Src-deficient cells to Foxm1 inhibition was markedly weaker, arguing that Foxm1 activity is largely compromised by prior loss of c-Src.…”
Section: Targeting Foxm1 Blocks Proliferation and Progression In Mode...supporting
confidence: 77%
“…We obtained similar results using NB-55 and NB-115, compounds that bind FOXM1 with high specificity and nanomolar affinity, enhancing its susceptibility to proteolysis and triggering proteasomal degradation (52). Similar to observations from myeloma, breast and ovarian cancer models (49,(53)(54)(55), both drugs caused dose-dependent suppression of proliferation and Foxm1 expression, while altering gene expression in a manner consistent with Foxm1 inhibition (Figure 6, D-F and Supplemental Figure 7, D and E). As with Foxm1 silencing, the response of c-Src-deficient cells to Foxm1 inhibition was markedly weaker, arguing that Foxm1 activity is largely compromised by prior loss of c-Src.…”
Section: Targeting Foxm1 Blocks Proliferation and Progression In Mode...supporting
confidence: 77%
“…FOXM1 regulates the metabolism of myeloma cells by upregulating glycolysis and OXPHOS. NB73, a small-compound inhibitor of FOXM1, inhibits MM cell growth by promoting FOXM1 degradation, suggesting that NB73 could become a promising OXPHOS-targeted drug [ 53 ]. Xiang et al reported that the expression of OXPHOS-associated genes is associated with higher PGC-1α expression; treatment with the PGC-1a inhibitor SR18292 was shown to significantly impair the proliferation and survival of MM cells due to dysfunction in OXPHOS metabolism [ 54 ].…”
Section: Mitochondrial Transfer Via Tnts: a Novel Cam-dr Conceptmentioning
confidence: 99%
“…The transcription factors FOXM1, HIF-1a and c-MYC also play a critical role during metabolic reprogramming of MM cells. The transcription factor forkhead box M1 (FOXM1) has been identified as a positive regulator of metabolism in MM (41). Cheng et al demonstrated that FOXM1 increases glucose uptake, lactate production, and oxygen consumption, promoting MM growth and survival (41).…”
Section: Glucose Metabolism In MMmentioning
confidence: 99%
“…The transcription factor forkhead box M1 (FOXM1) has been identified as a positive regulator of metabolism in MM (41). Cheng et al demonstrated that FOXM1 increases glucose uptake, lactate production, and oxygen consumption, promoting MM growth and survival (41). Treatment with 1,1-diarylethylene (NB73), a small FOXM1 inhibitory compound, suppresses MM in vitro and in vivo by enhancing the proteasomal degradation of FOXM1 (41).…”
Section: Glucose Metabolism In MMmentioning
confidence: 99%
See 1 more Smart Citation